Mejora de procesos con herramientas BPMS en empresa de tercerización de servicios financieros - Ismodes Ato, Carlos Arturo (2022)
This document shows the technical, management, continuous learning and ethical conduct capabilities to develop process automation projects with process management solutions, starting with the implementation of a technological product with the minimum required functionalities in the shortest possible time and gradually creating new versions until reaching the desired situation. The main challenges of improving the existing automated process were that: (1) the existing technological solution does not have the minimum required functionalities to be used by employees, (2) employees were not trained on the use of the system, there is no repository where instructions and audiovisual material on the use of the system can be located, and finally, (3) there were no reports or dashboards with the key indicators of the process. It is in this context that a process automation committee was created to propose, approve and implement initiatives to improve the automated process. The improvement of the automated process starts in September 2020, with the identification of the functional and technical gap of the automated process, and methodologically, it is decided to gradually implement the desired situation by delivering new versions every two weeks. Another very important aspect addressed during the implementation of the automated process was knowledge management by creating public repositories so that employees can access the instructions for use, videotaped training sessions and reports. Finally, I highlight as the main lessons learned: (1) Deliver technological products gradually, (2) Give biweekly visibility of the progress status, (3) Include key employees or system actors, and not only the Chief and (4) Do not timely transfer knowledge from the development team to the maintenance or support team for attention to events, incidents and problems.